ASSOCIATION BETWEEN FAMILY SUPPORT AND EXCLUSIVE BREASTFEEDING PRACTICE AMONG MOTHERS OF INFANTS AGED 0-6 MONTHS IN BEKASI CITY - Marella; Helda; Ristina Rosauli Harianja; Marella Marella; Helda Helda (Journal of Innovation Research and Knowledge, 2025)
Abstract: Family support is an important reinforcing factor in the success of exclusive breastfeeding. Support from family members may include physical, emotional, psychological, instrumental, and informational assistance that helps mothers maintain breastfeeding during the first six months of an infant's life. This study aimed to examine the association between family support and exclusive breastfeeding practice among mothers of infants aged 0-6 months in the working area of Pengasinan Public Health Center, Bekasi City. This study used a cross-sectional design involving 194 mothers of infants aged 0-6 months who were registered at integrated health posts (Posyandu). Respondents were selected using simple random sampling and interviewed using a structured questionnaire. Data were analyzed using univariate analysis, chi-square tests, and multivariable analysis to assess the association between family support and exclusive breastfeeding practice after controlling for covariates. The results showed that 45.9% of mothers practiced exclusive breastfeeding, while 72.7% reported receiving good family support. Mothers who received good family support were more likely to practice exclusive breastfeeding than those who received inadequate family support. After adjustment for covariates, family support remained significantly associated with exclusive breastfeeding practice, with an adjusted prevalence ratio of 4.111 (95% CI: 1.994-8.476; p = 0.0001). The most frequently reported form of support was family encouragement for mothers to breastfeed their infants as early as possible. This study concludes that family support is significantly associated with exclusive breastfeeding practice among mothers of infants aged 0-6 months. Health care providers should actively involve family members in breastfeeding education and promotion programs to strengthen maternal support systems and improve exclusive breastfeeding coverage.